DIGITIZATION AND INNOVATION IN HEALTHCARE SERVICES - Andreea BREAZU (Business Excellence and Management)
Innovation and digital technologies have caused major changes in most fields today, including health services. Thus, access to telemedicine, investigations with modern equipment and online scheduling improved the time spent by patients in receiving the services they needed. In this context, in the last two decades, the interest of academics and specialists in studying the complex relationship between digitization and innovation in the medical field has increased. Therefore, the purpose of this research is to highlight the conceptual links between "healthcare", "innovation" and "digitalization" in order to highlight the current concerns of this sector. Using a bibliometric analysis and the Web of Science database, the paper manages to analyze 650 scientific documents in which these concepts were found. The results of the survey highlight the fact that there was a high interest in research on the relationship between these concepts during the pandemic period. Also, the thematic map created identified specific clusters related to digitization and health. From a theoretical point of view, the research complements academic studies in this field and in particular extends bibliometric theories. From a practical point of view, this study provides valuable information to practitioners and decision-makers in the medical field, and especially to those who are in full development and digitalization process. As an element of originality, the paper identifies thematic groups that provide readers with information on emerging topics in this field.